Phylogeny, identification and pathogenicity of Lasiodiplodia associated with postharvest stem-end rot of coconut in Brazil - Rosado, André Wilson Campos (2014)
The coconut palm (Cocos nucifera L.) is one of the most important perennial tropical crops. Brazil is the fourth largest producer of coconut, after Indonesia, Philippines and India. Coconut production is limited by several factors, including diseases. Stem-end rot is the major postharvest disease of coconut in Brazil, causing great losses in all producing regions. This disease occurs in fruits after harvest and starts as a black rot in the peduncle that progresses to the entire fruit. The fungus Lasiodiplodia theobromae is the only species reported associated with this disease. However, an accurate study of this pathogen as the sole causal agent has never been carried out. In recent years, new species of Lasiodiplodia have been proposed after molecular studies, have demonstrated the existence of a species complex behind L. theobromae. Here the etiology of stem-end rot of C. nucifera was studied based on a combination of morphological characteristics with TEF1-α sequence data, aimed at re-evaluating the phylogenetic position of Lasiodiplodia involved in this disease and to assess the pathogenicity of the taxa found. Green coconuts with stem-end rot symptoms and signs of the pathogen were collected in Viçosa, state of Minas Gerais. In addition, isolates were obtained from Bahia, Ceará and Paraíba states. Single-spore cultures were obtained and stored. These had their DNA extracted and their TEF1-α region was sequenced. From the results of the phylogenetic analyses, one isolate of each species was separated for the morphological characterization and pathogenicity tests. Six species were identified: Lasiodiplodia egyptiacae, L. pseudotheobromae, L. theobromae, L. viticola and two will be proposed as new species (Lasiodiplodia sp. 1 and Lasiodiplodia sp. 2). All species were distinguished morphologically and phylogenetically and were proven to be pathogenic to coconut. Despite its importance, the etiology of stem-end rot of coconut has been traditionally neglected by science and remained somewhat obscure. This work resulted the first reports worldwide of the presence of three different species of Lasiodiplodia as causal agents of stem-end rot of coconut. Additionally, two previously undescribed species, which will be proposed as new, were found. Little has been investigated about the Lasiodiplodia complex in Brazil. The results of this study may be helpful for further studies on management measures, quarantine programs or on development of stem-end rot resistant coconut varieties.